2021
DOI: 10.1002/nop2.656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of open versus closed endotracheal suctioning on intracranial pressure in severe brain‐injured children: Study protocol for a randomized controlled trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In preterm infants, autoregulation of cerebral blood ow is not well developed, and direct impact of blood ow on the cerebrovascular wall can cause rupture and bleeding. It has been shown that altered cerebral blood ow occurs in neonates after mechanical ventilation, increasing the risk of brain injury [16,17] . Different mechanical ventilation parameters are used depending on the condition of the patient, making it di cult to categorize mechanical ventilation as a single covariate.…”
Section: Discussionmentioning
confidence: 99%
“…In preterm infants, autoregulation of cerebral blood ow is not well developed, and direct impact of blood ow on the cerebrovascular wall can cause rupture and bleeding. It has been shown that altered cerebral blood ow occurs in neonates after mechanical ventilation, increasing the risk of brain injury [16,17] . Different mechanical ventilation parameters are used depending on the condition of the patient, making it di cult to categorize mechanical ventilation as a single covariate.…”
Section: Discussionmentioning
confidence: 99%